2010
DOI: 10.1007/s00181-010-0441-0
|View full text |Cite
|
Sign up to set email alerts
|

Digging out the PPP hypothesis: an integrated empirical coverage

Abstract: We use several popular tests to test the validity of the Purchasing Power Parity (PPP) hypothesis. In particular, we analyze four classes of tests-standard univariate unit root tests, co-integration, panel unit root tests, and unit root tests for nonlinear frameworks-for a dataset consisting of 20 bilateral exchange rates. Through this approach, we ascertain the effectiveness of each methodology in assessing the validity of PPP. Overall, our results suggest little evidence to support PPP. Among the conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…However, without appropriate treatment, interdependence across the countries could lead to violations of the cross‐sectional independence assumption in the panel analysis. In particular, the existence of cross‐sectional correlation in the panel estimation model may result in a size distortion such that the econometric tests would be biased toward rejection of the null hypothesis of a nonstationary process (Bai and Ng ; Amornthum and Bonham ; de Carvalho and Júlio ).…”
Section: Introductionmentioning
confidence: 99%
“…However, without appropriate treatment, interdependence across the countries could lead to violations of the cross‐sectional independence assumption in the panel analysis. In particular, the existence of cross‐sectional correlation in the panel estimation model may result in a size distortion such that the econometric tests would be biased toward rejection of the null hypothesis of a nonstationary process (Bai and Ng ; Amornthum and Bonham ; de Carvalho and Júlio ).…”
Section: Introductionmentioning
confidence: 99%
“…RERs of the United Kingdom, United States, France, Germany and Japan for the period 1982 to 1997 and demonstrated that the PPP hypothesis fails. Carvalho and Julio (2012) analyzed the PPP theory for 20 OECD member economies using a large number of unit root tests. The authors failed to provide strong support for the PPP theory by using the standard time series unit root tests.…”
Section: Literature Surveymentioning
confidence: 99%
“…First, it is well documented in the literature that conventional panel unit root tests that do not consider CSD lead to serious size distortions. Allowing for CSD is especially important when testing for PPP, because RERs by construction contain two common components: the foreign price index, and the value of the numeraire currency, which naturally causes them to be cross-sectionally dependent (O' Connell, 1998;Carvalho and Julio, 2012). Second; if the panel unit root test leads to the rejection of the unit root null, then this does not mean that all of the series in the panel contain a unit root (Taylor and Sarno, 1998;Sarno and Taylor, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In practice we are often faced with the question whether economic time series are stationary (de Carvalho and Júlio, 2012). One of the most used tests for such a purpose is the test of Kwiatkowski et al.…”
Section: Preliminary Analysis Of Initial Claims Datamentioning
confidence: 99%